STUDY OF THE INFLUENCE OF ROAD RESISTANCE ON THE FUEL CONSUMPTION OF A PASSENGER CAR WITH AN AUTOMATIC TRANSMISSION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
One of the directions in the modern automotive industry is related to optimizing processes of the working cycle of internal combustion engines, which is related on another hand to reducing fuel consumption. This article presents calculation results of fuel consumption of a passenger car Honda Accord with automatic gearbox which are based on experimentally obtained power characteristics by using a chassis dynamometer DYNO COSBER. The fuel consumption was determined at different speeds of the car on a road without a slope and with 2%, 4% and 6% slope by using the chassis dynamometer and diagnostic equipment. The results of calculations about the influence of road resistances on fuel consumption were compared and analyzed with those obtained from measurements.